# |
ODE |
Mathematica |
Maple |
\[
{}3 x^{2} y^{4}+2 x y+\left (2 x^{3} y^{3}-x^{2}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{4}+2 y+\left (x y^{3}+2 y^{4}-4 x \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{3}-2 x^{2} y+\left (2 x y^{2}-x^{3}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 x^{2} y-3 y^{4}+\left (3 x^{3}+2 x y^{3}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{2}+2 x^{2} y+\left (2 x^{3}-x y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }-a y = 1+x
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y = {\mathrm e}^{-x}
\] |
✓ |
✓ |
|
\[
{}\cos \left (x \right )^{2} y^{\prime }+y = \tan \left (x \right )
\] |
✓ |
✓ |
|
\[
{}\left (1+x \right ) y^{\prime }-n y = {\mathrm e}^{x} \left (1+x \right )^{n +1}
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+1\right ) y^{\prime }+2 x y = 4 x^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+\frac {y}{x} = y^{6} x^{2}
\] |
✓ |
✓ |
|
\[
{}1+y^{2} = \left (\arctan \left (y\right )-x \right ) y^{\prime }
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+\frac {2 y}{x} = 3 x^{2} y^{{1}/{3}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+\frac {x y}{-x^{2}+1} = x \sqrt {y}
\] |
✓ |
✓ |
|
\[
{}3 x \left (-x^{2}+1\right ) y^{2} y^{\prime }+\left (2 x^{2}-1\right ) y^{3} = a \,x^{3}
\] |
✓ |
✓ |
|
\[
{}\left (x +y\right )^{2} y^{\prime } = a^{2}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }-y = \sqrt {x^{2}+y^{2}}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }-y = x \sqrt {x^{2}+y^{2}}
\] |
✓ |
✓ |
|
\[
{}\sec \left (x \right )^{2} \tan \left (y\right )+\sec \left (y\right )^{2} \tan \left (x \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}-x^{2} y\right ) y^{\prime }+y^{2}+x y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+\frac {\left (1-2 x \right ) y}{x^{2}} = 1
\] |
✓ |
✓ |
|
\[
{}3 y^{\prime }+\frac {2 y}{1+x} = \frac {x^{3}}{y^{2}}
\] |
✓ |
✓ |
|
\[
{}2 x -y+1+\left (2 y-x -1\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+\frac {y}{\sqrt {-x^{2}+1}} = \frac {x +\sqrt {-x^{2}+1}}{\left (-x^{2}+1\right )^{2}}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+\frac {y^{2}}{x} = y
\] |
✓ |
✓ |
|
\[
{}x \left (-a^{2}+x^{2}+y^{2}\right )+y \left (x^{2}-y^{2}-b^{2}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+\frac {4 x y}{x^{2}+1} = \frac {1}{\left (x^{2}+1\right )^{3}}
\] |
✓ |
✓ |
|
\[
{}x^{2} y-\left (y^{3}+x^{3}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x \left (-x^{2}+1\right ) y^{\prime }+\left (2 x^{2}-1\right ) y = a \,x^{3}
\] |
✓ |
✓ |
|
\[
{}x^{2}+y^{2}+1-2 x y y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x +y y^{\prime } = m \left (x y^{\prime }-y\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y \cos \left (x \right ) = y^{n} \sin \left (2 x \right )
\] |
✓ |
✓ |
|
\[
{}\left (1+x \right ) y^{\prime }+1 = 2 \,{\mathrm e}^{y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x^{3} y^{3}-x y
\] |
✓ |
✓ |
|
\[
{}y+\left (a \,x^{2} y^{n}-2 x \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\left (1+6 y^{2}-3 x^{2} y\right ) y^{\prime } = 3 x y^{2}-x^{2}
\] |
✓ |
✓ |
|
\[
{}y \left (x^{2}+y^{2}+a^{2}\right ) y^{\prime }+x \left (-a^{2}+x^{2}+y^{2}\right ) = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2} y^{3}+x y\right ) y^{\prime } = 1
\] |
✓ |
✓ |
|
\[
{}y y^{\prime } = a x
\] |
✓ |
✓ |
|
\[
{}\sqrt {a^{2}+x^{2}}\, y^{\prime }+y = \sqrt {a^{2}+x^{2}}-x
\] |
✓ |
✓ |
|
\[
{}\left (x +y\right ) y^{\prime }+x -y = 0
\] |
✓ |
✓ |
|
\[
{}y y^{\prime }+b y^{2} = a \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}2 x y+\left (y^{2}-x^{2}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}-x y^{\prime }+y = b \left (1+x^{2} y^{\prime }\right )
\] |
✓ |
✓ |
|
\[
{}3 y+2 x +4-\left (4 x +6 y+5\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{3} y^{3}+x^{2} y^{2}+x y+1\right ) y+\left (x^{3} y^{3}-x^{2} y^{2}-x y+1\right ) x y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 x^{2} y^{2}+y-\left (x^{3} y-3 x \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{2}+x^{2} y^{\prime } = x y y^{\prime }
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+\frac {n y}{x} = a \,x^{-n}
\] |
✓ |
✓ |
|
\[
{}\left (x -y\right )^{2} y^{\prime } = a^{2}
\] |
✓ |
✓ |
|
\[
{}x y \left (-x y^{\prime }+y\right ) = x +y y^{\prime }
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+2 x y = x^{2}+y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } \sqrt {x} = \sqrt {y}
\] |
✓ |
✓ |
|
\[
{}y+x +x y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\left (x y+1\right ) y-x y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\sin \left (x \right ) y^{\prime }-y \cos \left (x \right )+y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y-x +\left (x +y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x +y y^{\prime }+\frac {x y^{\prime }-y}{x^{2}+y^{2}} = 0
\] |
✓ |
✓ |
|
\[
{}x^{3}+3 x y^{2}+\left (3 x^{2} y+y^{3}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+y = y^{2} \ln \left (x \right )
\] |
✓ |
✓ |
|
\[
{}\left (-x^{2}+1\right ) y^{\prime }-2 x y = -x^{3}+x
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }-y-\cos \left (\frac {1}{x}\right ) = 0
\] |
✓ |
✓ |
|
\[
{}x +y y^{\prime } = m \left (x y^{\prime }-y\right )
\] |
✓ |
✓ |
|
\[
{}x \cos \left (y\right )^{2} = y \cos \left (x \right )^{2} y^{\prime }
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = {\mathrm e}^{x -y}+x^{2} {\mathrm e}^{-y}
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime }+y = 1
\] |
✓ |
✓ |
|
\[
{}2 y+\left (x^{2}+1\right ) \arctan \left (x \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x y^{2}+x +\left (x^{2} y+y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = {\mathrm e}^{x +y}+x^{2} {\mathrm e}^{y}
\] |
✓ |
✓ |
|
\[
{}\left (3+2 \sin \left (x \right )+\cos \left (x \right )\right ) y^{\prime } = 1+2 \sin \left (y\right )+\cos \left (y\right )
\] |
✓ |
✓ |
|
\[
{}\frac {\cos \left (y\right )^{2} y^{\prime }}{x}+\frac {\cos \left (x \right )^{2}}{y} = 0
\] |
✓ |
✓ |
|
\[
{}\left (1+{\mathrm e}^{x}\right ) y y^{\prime } = \left (1+y\right ) {\mathrm e}^{x}
\] |
✓ |
✓ |
|
\[
{}\csc \left (x \right ) \ln \left (y\right ) y^{\prime }+x^{2} y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {\sin \left (x \right )+x \cos \left (x \right )}{y \left (2 \ln \left (y\right )+1\right )}
\] |
✓ |
✓ |
|
\[
{}\cos \left (y\right ) \ln \left (\sec \left (x \right )+\tan \left (x \right )\right ) = \cos \left (x \right ) \ln \left (\sec \left (y\right )+\tan \left (y\right )\right ) y^{\prime }
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}-x^{2} y\right ) y^{\prime }+y^{2}+x y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}\left (\sin \left (y\right )+y \cos \left (y\right )\right ) y^{\prime }-\left (2 \ln \left (x \right )+1\right ) x = 0
\] |
✓ |
✓ |
|
\[
{}3 \,{\mathrm e}^{x} \tan \left (y\right )+\left (1-{\mathrm e}^{x}\right ) \sec \left (y\right )^{2} y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}-x y^{\prime }+y = a \left (y^{2}+y^{\prime }\right )
\] |
✓ |
✓ |
|
\[
{}\left (x +y-1\right ) y^{\prime } = x +y+1
\] |
✓ |
✓ |
|
\[
{}\left (2 x +2 y+1\right ) y^{\prime } = x +y+1
\] |
✓ |
✓ |
|
\[
{}\left (2 x +3 y-5\right ) y^{\prime }+2 x +3 y-1 = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+y^{2}\right ) y^{\prime } = x y+x^{2}
\] |
✓ |
✓ |
|
\[
{}\left (x \cos \left (\frac {y}{x}\right )+y \sin \left (\frac {y}{x}\right )\right ) y-\left (y \sin \left (\frac {y}{x}\right )-x \cos \left (\frac {y}{x}\right )\right ) x y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x^{2}-y^{2}+2 x y y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {y}{x}+\tan \left (\frac {y}{x}\right )
\] |
✓ |
✓ |
|
\[
{}\left (2 x -2 y+5\right ) y^{\prime }-x +y-3 = 0
\] |
✓ |
✓ |
|
\[
{}x +y+1-\left (2 x +2 y+1\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{2} = \left (x y-x^{2}\right ) y^{\prime }
\] |
✓ |
✓ |
|
\[
{}x \sin \left (\frac {y}{x}\right ) y^{\prime } = y \sin \left (\frac {y}{x}\right )-x
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+y^{2}\right ) y^{\prime } = x y
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime }+y \left (x +y\right ) = 0
\] |
✓ |
✓ |
|
\[
{}2 y^{\prime } = \frac {y}{x}+\frac {y^{2}}{x^{2}}
\] |
✓ |
✓ |
|
\[
{}\left (6 x -5 y+4\right ) y^{\prime }+y-2 x -1 = 0
\] |
✓ |
✓ |
|
\[
{}\left (x -3 y+4\right ) y^{\prime }+7 y-5 x = 0
\] |
✓ |
✓ |
|
\[
{}\left (2 x +4 y+3\right ) y^{\prime } = 2 y+x +1
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }-y = \sqrt {x^{2}+y^{2}}
\] |
✓ |
✓ |
|
\[
{}x \left (x^{2}+3 y^{2}\right )+y \left (y^{2}+3 x^{2}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x^{2}+3 y^{2}-2 x y y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {2 x -y+1}{x +2 y-3}
\] |
✓ |
✓ |
|